Coronal Multi-channel Polarimeter at the Lomnicky Peak Observatory. Issue Volume 8:Issue S300(2013) (6th January 2014) - Schwartz, P.; Ambroz, J.; Gömöry, P.; Kozák, M.; Kučera, A.; Rybák, J.; Tomczyk, S.; Sewell, S.; Aumiller, P.; Summers, R.; Sutherland, L.; Watt, A.
Abstract: Coronal Multi-channel Polarimeter (CoMP-S), developed by HAO/NCAR, has been introduced to regular operation at the Lomnicky Peak Observatory (High Tatras in northern Slovakia, 2633 m a.s.l.) of the Astronomical Institute of Slovak Academy of Sciences. We present here the technical parameters of the current version of the instrument and its potential for observations of prominences in the visual and near-IR spectral regions. The first results derived from observations of prominences in the Hα emission line taken during a coordinated observing campaign of several instruments in October 2012 are shown here.